Oxygenated Secondary Metabolites from Endophytic Fungi Isolated From Ocimum sanctum - Mohammad Shoeb; Mohammad Shaheen Uddin Khandaker; Nilufar Nahar (Journal of Basic & Applied Sciences, 2015)
Ocimum sanctum Linn (Tulsi), an important medicinal plant of Bangladesh is used for antimicrobial, anti-inflammatory and antiulcer activities. Eleven endophytic fungi were isolated from O. sanctum. The fungal strain, labeled as OS-005, was cultivated at large scale on the potato dextrose agar semi solid medium and was extracted with ethyl acetate. Repeated column chromatography of the parent extract by normal phase silica gel and one of its fraction by Sephadex LH-20 afforded linoleic acid, R (-)-glycerol monolinoleate, 9,10,11-trihydroxy-(12Z)-12-octadecenoic acid, ergosterol, ergosterol peroxide, 1,8-O-dimethylaverantin, coriloxin, and a new natural product named sanctumol. The structures of these compounds were elucidated unequivocally by UV, IR, MS and a series of 1D & 2D NMR analyses.